Analisis Laporan Beban Kerja Dosen Pendidikan Agama Islam (PAI) pada Bidang Penelitian dengan menggunakan Metode Clustering - Pratama, Muhammad Egy; Kusrini, Kusrini; Agastya, I Made Artha (Prodi Pendidikan Agama Islam IAINU Kebumen, 2025)
This study aims to classify research activities of Islamic Education lecturers based on Lecturer Workload Reports using the K-Means clustering method. The dataset includes research activities of PAI lecturers at UIN Sultan Aji Muhammad Idris Samarinda over the past three academic years. Classification was conducted by identifying publication types based on keywords and summarizing each lecturer’s activity. The results show variations in productivity, with many activities falling into the “others” category due to the lack of explicit publication descriptions. The K-Means method grouped lecturers into three clusters: Active, Moderately Active, and Less Active, based on the number of activities and total SKS. These findings can assist faculty leaders in formulating human resource development strategies and enhancing lecturers’ performance in supporting key performance indicators (KPI) and accreditation standards.